(NnEOKON^ENNYE ROMANY I POWESTI(B: [1842-1856] / s (N~ASTX (B6s - (NnEKRASOW(B, (NnIKOLAJ aLEKSEEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1966)
(Nw [ESTOJ TOM WO[LI NEOKON^ENNYE ROMANY I POWESTI (B1842-1856 (NGG(B.s
rus
Keywords: (NpOWESTX(B, (NRASSKAZYs; (NrOMANYs